Home-Based Exercise Prehabilitation During Preoperative Treatment for Pancreatic Cancer Is Associated With Improvement in Physical Function and Quality of Life. (December 2019) - Ngo-Huang, An; Parker, Nathan H.; Bruera, Eduardo; Lee, Rebecca E.; Simpson, Richard; O'Connor, Daniel P.; Petzel, Maria Q. B.; Fontillas, Rhodora C.; Schadler, Keri; Xiao, Lianchun; Wang, Xuemei; Fogelman, David; et al.
Purpose: To investigate relationships among physical activity, changes in physical function, and health-related quality of life (HRQOL) among patients with pancreatic adenocarcinoma enrolled in a home-based exercise prehabilitation program.Methods: Patients with resectable pancreatic adenocarcinoma receiving preoperative chemotherapy and/or chemoradiation were enrolled on this prospective, single-arm trial and were advised to perform ≥60 minutes each of moderate-intensity aerobic exercise and strengthening exercise weekly. Activity was measured via self-report and accelerometers, including moderate-to-vigorous physical activity (MVPA), light physical activity (LPA), and sedentary activity (SA). Physical function measures at baseline and restaging follow-up included 6-minute walk test (6MWT), 5 times sit-to-stand (5×STS), handgrip strength (HGS), 3-m walk for gait speed (GS), and the PROMIS Physical Function Short Form. HRQOL was measured via the FACT-Hep questionnaire.Results: Fifty participants with mean age 66 years (standard deviation = 8 years) were enrolled. The 6MWT, 5×STS, and GS significantly improved from baseline to restaging follow-up (P=.001, P=.049, and P=.009, respectively). Increases in self-reported aerobic exercise, weekly MVPA, and LPA were associated with improvement in 6MWT (β=.19, P=.048; β=.18, P=.03; and β=.08, P=.03, respectively) and self-reported physical functioning (β=.02, P=.03; β=.03, P=.005; and β=.01, P=.02, respectively). Increased weekly LPA was associated with increased HRQOL (β=.03, P=.02). Increased SA was associated with decreased HRQOL (β=-.02, P=.01).Conclusions: Patients with potentially resectable pancreatic cancer exhibit meaningful improvement in physical function with prehabilitation; physical activity was associated with improved physical function and HRQOL. These data highlight the importance of physical activity during treatment for pancreatic cancer.